Recent Findings and Open Issues concerning the Seismic Behaviour of Masonry Infill Walls in RC Buildings - André Furtado; Maria Teresa de Risi (Advances in Civil Engineering)
The extension of the damages observed after the last major earthquakes shows that the seismic risk mitigation of infilled reinforced concrete structures is a paramount topic in seismic prone regions. In the assessment of existing structures and the design of new ones, the infill walls are considered as nonstructural elements by most of the seismic codes and, generally, comprehensive provisions for practitioners are missing. However, nowadays, it is well recognized by the community the importance of the infills in the seismic behaviour of the reinforced concrete structures. Accurate modelling strategies and appropriate seismic assessment methodologies are crucial to understand the behaviour of existing buildings and to develop efficient and appropriate mitigation measures to prevent high level of damages, casualties, and economic losses. The development of effective strengthening solutions to improve the infill seismic behaviour and proper analytical formulations that could help design engineers are still open issues, among others, on this topic. The main aim of this paper is to provide a state-of-the-art review concerning the typologies of damages observed in the last earthquakes where the causes and possible solutions are discussed. After that, a review of in-plane and out-of-plane testing campaigns from the literature on infilled reinforced concrete frames are presented as well as their relevant findings. The most common strengthening solutions to improve the seismic behaviour are presented, and some examples are discussed. Finally, a brief summary of the modelling strategies available in the literature is presented.